Soluble extracellular polymeric substance (SEPS) of histo-blood group antigen (HBGA) expressing bacterium Sphingobacterium sp. SC015 influences the survival and persistence of norovirus on lettuce. (February 2023) - Liao, Ningbo; Tang, Mengxuan; Chen, Lili; Tian, Peng; Wang, Dapeng; Cheng, Dongqing; Wu, Guoping
Abstract: Foodborne norovirus (NoV) outbreaks linked to leafy greens are common due to a lack of efficient strategies to prevent NoV spread from contaminated surfaces. We previously found that Sphingobacterium sp. SC015 in lettuce phyllosphere expresses histo-blood group antigen (HBGA)-like substances in soluble extracellular polymeric substances (SEPS) that contribute to NoV adherence on lettuce. Here, we extracted SEPS from bacterium SC015 (SEPS-SC015), analyzed their chemical composition, and examined their roles in the survival and protection of NoV and surrogates [murine norovirus (MNV-1) and Tulane virus (TuV)] on lettuce. Presence of SEPS-SC015 significantly increased survival and persistence of human NoV (HuNoV), MNV-1, and TuV at days 7 and 14, compared with virus alone. HuNoV, TuV, and MNV-1 seeded with SEPS-SC015 were more resistant to heat (70 °C, 2 min) than these viruses alone. SEPS-SC015 also increased viral resistance to sodium hypochlorite inactivation by treatment with 30 and 300 ppm bleach at 26 °C for 10 min. However, SEPS-SC015 was not effective at protecting these viruses under UV inactivation. Binding of TuV to SC015 bacteria and SEPS-SC015, visualized using transmission electron microscopy, suggests that protection might be related to direct interaction between SEPS-SC015 and viral particles. This study provides important insights that will help inform strategies to improve food safety. Graphical abstract: Image 1 Highlights: The Sphingobacterium sp . SC015 in lettuce phyllosphere expresses histo-blood group antigen (HBGA) substances. The HBGA substances are mainly distributed in the soluble extracellular polymeric substance (SEPS-SC015). SEPS-SC015 increases the survival and persistence of HuNoV, MNV-1, and TuV. SEPS-SC015 confers protective effects on HuNoV, MNV-1 and TuV against heat and chemical inactivation. The protection might be related to affinity interactions between SEPS-SC015 and viral particle.